Influence of electron-ion collisions on Buneman instability in fully ionized plasma - Rostomyan, E. V. (Physics of plasmas, 2016)
The stability of a fully ionized plasma with a relative electron-ion (e-i) motion is considered taking into account the e-i collisions of high level. The relative e-i drift speed is assumed to be much higher than the thermal spread of electrons, and in the absence of collisions the system is subject to the low frequency and strongly growing Buneman instability. The transport equation with the Landau collision integral is solved taking into account the dependence of the collision frequency on the velocity of colliding particles. The effective frequency of e-i collisions is determined as a function of the system parameters. It is shown that with an increase in the level of e-i collisions the Buneman instability gradually transforms to the instability of dissipative type. This transition is traced in detail. The dependence of the growth rate on collision frequency upon this transformation is obtained.